Preparation method and application of ferroelectric photoelectrode with vertical ordered nanorod array structure
By using vertically ordered nanopillar array structure in photoelectrochemical decomposition of water hydrogen production technology, the problem of low photogenerating charge recombination efficiency is solved, and the photogenerating charge recombination is achieved by using alumina template method and magnetron sputtering deposition technology. Efficient photoelectrochemical activity and solar-hydrogen conversion efficiency.
Patent Information
- Application Number
- CN202411233577.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-20
AI Technical Summary
In the existing photoelectrochemical decomposition of water hydrogen production technology, the rapid recombination of photogenerated charges leads to inefficiency, and the high band gap and low conductivity of inorganic ferroelectric materials limit their application in photoelectrocatalysis.
The ferroelectric photoelectrode with a vertically ordered nanopillar array structure is prepared by the alumina template method, combined with magnetron sputtering deposition and electrodeposition technology to form a metal platinum nanolayer and nickel support layer to enhance the light absorption and charge separation capabilities. .
The photoelectrochemical activity is significantly improved, the photocurrent density is increased by 20 times, the charge separation efficiency is increased by 200%, and the high-efficiency solar-to-hydrogen conversion efficiency of ferroelectric photoelectrodes is achieved.
Smart Images

Figure CN119162597A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, relates to a photoelectrode, and in particular to a preparation method and application of a ferroelectric photoelectrode with a vertical ordered nanocolumn array structure. Background Art
[0002] Energy consumption and environmental degradation have become one of the obstacles to economic and social development. Photoelectrochemical (PEC) water splitting hydrogen production technology only requires sunlight and water to produce green and clean energy hydrogen, and is an important direction for future energy development. However, the strong Coulomb attraction causes the photogenerated charges to recombine rapidly, which is a key factor that seriously restricts the efficiency of PEC water splitting hydrogen production. In view of this, domestic and foreign scholars started from the band bending theory and regulated the charge separation performance of the photoelectrode bulk and surface by constructing semiconductor PN junctions, heterogeneous junctions, crystal face junctions, etc., thereby enhancing the separation effect of photogenerated charges. In the above strategies, the built-in electric field at the surface interface of the photoelectrode material is the main driving force for the separation of photogenerated charges. It mainly relies on the potential energy difference (charge concentration difference) formed at the interface to conduct the body / interface charge statically and unidirectionally in the form of spontaneous diffusion. The built-in electric field formed by this river-like potential energy difference has obvious intrinsic disadvantages: its intensity is limited by the difference in charge concentration; its range of action is limited by the junction interface, and the bulk charges far from the interface are easily affected by the Coulomb force and spontaneously recombine; in terms of maintenance time, as the photogenerated charges accumulate, the charge concentration difference is easily neutralized, and the built-in electric field generated by it tends to disappear. Therefore, in order to meet the demand for efficient suppression of photogenerated charge recombination, the key to material design in the PEC field is to simultaneously achieve high intensity, expanded range of action, and long-term maintenance of the built-in electric field.
[0003] The crystal structure of inorganic ferroelectric materials has a polar unit cell, which is formed by the displacement of cations beyond the anion center, and can produce spontaneous and permanent electric polarization (ferroelectric polarization), thereby forming polarized charge distributions of opposite electrical properties on two opposite crystal planes of the ferroelectric material. This polarized charge is in a high-energy state and can easily affect the distribution of charged ions around it. Therefore, the built-in electric field of surface charge modulation can be controllably adjusted for the design of materials in the field of PEC hydrogen production. However, inorganic ferroelectrics have a wide band gap and poor conductivity, resulting in an extremely limited number of available photogenerated carriers, which inhibits their application in photoelectrocatalytic systems. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to disclose a ferroelectric photoelectrode with a vertical ordered nanorod array structure and a preparation method thereof.
[0005] Technical Solution
[0006] The present invention utilizes a simple and controllable alumina template method to spin-coat a ferroelectric sol into an alumina template, and then deposits a conductive metal platinum nanolayer on the surface of the alumina template filled with the ferroelectric sol by a magnetron sputtering deposition method, and also utilizes an electrodeposition method to deposit a metal support layer of nickel on the surface of the platinum nanolayer, and finally removes aluminum and aluminum oxide to obtain a vertical ordered nanocolumn array structure photoelectrode. This vertical ordered nanocolumn array has a light trapping structure that can increase light absorption. In addition, the nanocolumns with a high aspect ratio structure not only ensure that the ferroelectric material is thick enough to absorb sunlight to generate enough carriers, but also greatly reduce the distance that the generated carriers migrate to the material surface (migration along the nanocolumn diameter direction), and extremely well regulate the clamping effect between the light absorption efficiency and the photogenerated charge separation efficiency of the ferroelectric photoelectrode.
[0007] A method for preparing a ferroelectric photoelectrode with a vertical ordered nanocolumn array structure comprises the following steps:
[0008] (1) Preparation of ferroelectric Pb(Zr 0.2 Ti 0.8 )O3(PZT)sol
[0009] (a) dissolving 2.17-6.17 g (CH3COO)2Pb·3H2O in 15 g glacial acetic acid (CH3COOH), dehydrating to 10 g at 150-250° C., preferably 200° C., and cooling to room temperature to obtain a lead sol;
[0010] (b) 0.53-1.53 g C 12 H 28 O4Zr (70wt%) and 14.13g ethylene glycol monomethyl ether (C3H8O2) were stirred and mixed evenly, and 1.7-4.7g C 16 H 36 O4Ti, then add 0.2-1ml of chelating agent acetylacetone (C5H8O2) to obtain zirconium titanium (ZT) sol;
[0011] (c) mixing 1-3 ml of deionized water (>18 MΩ) and an equal volume of ethylene glycol monomethyl ether (C3H8O2) to obtain a hydrolyzed sol;
[0012] (d) Add ZT sol to lead sol under low-speed stirring and continue stirring for 1 hour, then add hydrolyzed sol drop by drop and continue stirring for 2 to 6 hours, and age at room temperature for 12 to 48 hours to obtain a clear ferroelectric Pb(Zr 0.2 Ti 0.8 )O3(PZT) sol;
[0013] (2) Spin coating of PZT sol to fill the alumina template
[0014] The PZT sol is spin-coated and deposited on the surface of the circular alumina template, and the working parameters of the coating machine are: low speed 500 rpm for 5 seconds, high speed 3000-6000 rpm for 25 seconds; after each coating, the alumina template is first dried on a hot plate at 150-250°C for 2-6 minutes, and then annealed in an air environment at 400-700°C for 4-10 minutes, preferably dried at 200°C for 4 minutes and then annealed in an air environment at 580°C for 6 minutes; repeat 2-10 times to obtain a cylindrical alumina template with PZT filled in the pore wall and hollow in the center;
[0015] The circular alumina template is a laminated sheet with a base layer of metal aluminum and a surface layer of aluminum oxide. The surface of the aluminum oxide surface layer is distributed with a number of cylindrical holes of uniform size, with a pore diameter of 60 to 150 nm and an adjustable range, and a pore depth of 300 to 1000 nm and an adjustable range without penetrating the base layer.
[0016] The centrifugal force of the glue-spinning machine is used to make the PZT sol adhere to the wall of the cylindrical alumina hole, and the center of the cylinder remains hollow;
[0017] (3) Depositing a metal platinum nanolayer on the PZT surface and in the center of the PZT nanocolumn, and then electro-depositing metal nickel on the platinum surface as a supporting layer
[0018] ① Magnetron sputtering deposition of metal platinum Pt, the working parameters of the magnetron sputtering deposition instrument are: DC power supply, sputtering power of 10-30W, room temperature, working gas pressure of 0.5-0.9Pa, argon flow rate of 40-60sccm, and sputtering time of 1-5min;
[0019] ② Constant current electrochemical deposition of nickel Ni to obtain a nickel support layer. The electroplating solution contains 0.38M NiSO4, 0.12M NiCl2 and 0.5M H3BO3. The aluminum base layer of the alumina template does not contact the electroplating solution, only the PZT spin-coated surface is in contact. The deposition is carried out at a low current of 20mA for 1 to 3h → at a high current of 40 to 50mA for 5 to 10h → at 200mA for 1 to 5h.
[0020] (4) Remove the aluminum base layer and the aluminum oxide template
[0021] The aluminum base layer of the aluminum oxide template obtained in step (3) is placed in a mixed solution of CuCl2 / HCl (the volume ratio of water to concentrated hydrochloric acid is 1:1, and the concentration of CuCl2 is 0.15M), and the aluminum base layer is continuously washed away, and the sample surface on which the metal nickel is deposited does not contact the mixed solution of CuCl2 / HCl;
[0022] The alumina template after removing the aluminum base layer was turned over, with the metal nickel support layer facing downward, and completely placed in a 2M NaOH solution. It was allowed to stand at room temperature for 4 to 12 hours, and the alumina template was removed to obtain a ferroelectric PZT photoelectrode with a vertical ordered nanocolumn array structure.
[0023] The alumina template of the present invention is prepared by a secondary oxidation method, and the steps are as follows:
[0024] A. Clean the aluminum sheet, use the aluminum sheet as the anode and the lead plate as the cathode, in a mixed solution of perchloric acid HClO4 and ethanol C2H5OH with a volume ratio of 1:7, magnetic stirring at -10°C, polishing at a voltage of 20V for 2 to 7 minutes, and remove the surface oxide layer to obtain a mirror-polished aluminum sheet;
[0025] B. Using a polished aluminum sheet as an anode and a lead plate as a cathode, oxidation is performed in a 0.3M oxalic acid aqueous solution at 5°C and a voltage of 40V for 4 to 12 hours to obtain a primary oxide layer; placing the aluminum sheet containing the primary oxide layer in a mixed solution containing 6wt.% phosphoric acid H3PO4 and 1.8wt.% chromic acid H2CrO4 for corrosion treatment at 60°C for 8 to 15 hours to remove the primary oxide layer and obtain an aluminum sheet with nano-scale pits on the surface;
[0026] C. An aluminum sheet with nano-pits on the surface is used as the anode and a lead plate as the cathode. A secondary oxidation is performed in a 0.3M oxalic acid aqueous solution at a voltage of 40V and a temperature of 5°C for 10 to 40 min to obtain an initial alumina template. The initial alumina template is transferred to a 5wt.% dilute phosphoric acid solution and immersed at 45°C for 20 to 50 min to perform pore expansion to varying degrees. The template is then rinsed with deionized water to obtain an alumina template with controllable pore size.
[0027] The vertical ordered nanocolumn array structure ferroelectric photoelectrode prepared by the method described in the present invention has the morphology of a vertical ordered nanocolumn array structure supported by metal nickel, wherein the metal nickel is the electrode support layer, and its structure is a combination of a metal nickel planar layer and a metal nickel nanocolumn array layer; the metal platinum nanolayer tightly attached to the metal nickel nanocolumn array layer is the bottom electrode layer; the PZT nanolayer is tightly attached to the platinum nanolayer, and the PZT nanolayer is an extremely vertically ordered PZT nanocolumn array structure.
[0028] Another object of the present invention is to apply the prepared vertical ordered nanorod array structure ferroelectric photoelectrode to efficient PEC water decomposition to produce hydrogen.
[0029] The prepared photoelectrode was used as the working electrode, platinum sheet as the counter electrode, Ag / AgCl as the reference electrode, and the electrolyte was 0.5M Na2SO4 (pH 6.8) aqueous solution. A xenon lamp with an AM1.5G filter was used as the light source, and the light intensity was adjusted to 100 mW / cm 2 , and conduct photoelectrochemical tests.
[0030] Due to the effective light trapping effect of the vertically ordered three-dimensional nanorods, the light absorption range can be extended to the visible light band, greatly improving the charge carrier density of the PZT photoelectrode. Through the regulation of the method described in the present invention, the photoelectrode exhibits excellent photoelectrochemical activity, and its photocurrent density reaches -400μA / cm 2 (0V vs RHE), is a planar structure PZT nanolayer photoelectrode under the same test conditions (-20μA / cm 2 Compared with the planar structure of the PZT nanolayer photoelectrode, the charge separation efficiency of the photoelectrode is increased by 200% under the control of the method of the present invention.
[0031] In this specification, the term "PZT" is Pb(Zr 0.2 Ti 0.8 )O3, the two can be used interchangeably.
[0032] In this specification, the term "NR" is an abbreviation of "nanorodial", and the two can be used interchangeably.
[0033] In this specification, the term "NRs" is an abbreviation of "nanorodial arrays", and the two can be used interchangeably.
[0034] Beneficial Effects
[0035] The preparation process of the present invention is finely controllable, the operation steps are simple, and the constructed vertical ordered nanocolumn array structure PZT photoelectrode has a nanocolumn structure that can be finely controlled. The vertical ordered three-dimensional nanorod array structure can greatly increase the photogenerated charge carrier density, and each PZT nanocolumn will produce strong and lasting spontaneous polarization, thereby causing a high-energy polar charge induced electric field along the nanocolumn diameter direction (compared to the column height direction, the carrier movement distance in the column diameter direction is shorter). The vertical ordered three-dimensional PZT nanorod array structure with visible light absorption and the polar charge induced electric field coupling synergistically endow this photoelectrode with a long-lasting and rapid photogenerated charge separation ability, thereby greatly increasing the solar energy-hydrogen energy conversion efficiency of the ferroelectric photoelectrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 .Schematic diagram of the controllable preparation process of PZT nanocolumn structure.
[0037] Figure 2 .(A) Low-magnification SEM top view of the PZT planar structure; (B) High-magnification SEM top view of the PZT planar structure, with the inset being its cross-sectional SEM image; (C) Low-magnification SEM top view of the PZT nanocolumn structure; (D) High-magnification SEM top view of the PZT nanocolumn structure, with the inset being its cross-sectional SEM image.
[0038] Figure 3.(A) XRD patterns of PZT nanorods and PZT planar structures (ITO substrate); (B) Hysteresis loop diagram of PZT nanorods.
[0039] Figure 4 .(A) IV curves and (B) bias-induced photoelectric conversion efficiency (ABPE) curves of PZT nanorods and PZT planar structures (ITO substrate). DETAILED DESCRIPTION
[0040] The following is a detailed description of an embodiment of the present invention in conjunction with the accompanying drawings. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.
[0041] Example 1
[0042] This embodiment provides a method for preparing a vertically ordered ferroelectric PZT nanorod array. Figure 1 Schematic diagram of the preparation process of the vertical ordered ferroelectric PZT nanorod array of this embodiment.
[0043] A method for preparing a ferroelectric photoelectrode with a vertical ordered nanocolumn array structure comprises the following steps:
[0044] (1) Preparation of alumina template
[0045] The aluminum sheet was cleaned, and the aluminum sheet was used as the anode and the lead plate as the cathode. The aluminum sheet was placed in a mixed solution of perchloric acid HClO4 and ethanol C2H5OH with a volume ratio of 1:7, and magnetic stirring was performed at -10°C, and the voltage was 20V for 2 minutes to remove the surface oxide layer to obtain a mirror-polished aluminum sheet.
[0046] The polished aluminum sheet is used as an anode and the lead plate is used as a cathode. The aluminum sheet is oxidized in a 0.3M oxalic acid aqueous solution at 5°C, the voltage is 40V, and the oxidation time is 4h to obtain a primary oxide layer; the aluminum sheet containing the primary oxide layer is placed in a mixed solution of 6wt.% phosphoric acid H3PO4 and 1.8wt.% chromic acid H2CrO4 for corrosion treatment at 60°C for 8h to remove the primary oxide layer to obtain an aluminum sheet with nano-pits on the surface;
[0047] An aluminum sheet with nano-pits on the surface was used as an anode and a lead plate was used as a cathode. The aluminum sheet was oxidized in a 0.3M oxalic acid aqueous solution at 5°C, with a voltage of 40V and an oxidation time of 10min to obtain an initial aluminum oxide template. The template was then transferred to a 5wt.% dilute phosphoric acid solution and immersed at 45°C for 20min to expand the pores. The template was then rinsed with deionized water to obtain an aluminum oxide template.
[0048] (2) Preparation of ferroelectric Pb(Zr 0.2 Ti 0.8)O3(PZT)sol
[0049] 2.17 g (CH3COO)2Pb·3H2O (99.99%) was dissolved in 15 g CH3COOH and dehydrated to 10 g at 150°C to obtain lead sol;
[0050] 0.53 g C 12 H 28 O4Zr (70wt%) and 14.13g C3H8O2 were stirred and mixed evenly, and 1.7g C 16 H 36 O4Ti, and then add 0.2ml of chelating agent (C5H8O2) to prepare zirconium titanium (ZT) sol;
[0051] 1 ml of deionized water (>18 MΩ) and an equal volume of C3H8O2 were mixed to obtain a hydrolyzed sol;
[0052] After the lead sol is cooled to room temperature, the ZT sol is added to the lead sol under low-speed stirring. After stirring for one hour, the hydrolyzed sol is added dropwise and stirred for 2 hours. The sol is aged at room temperature for 12 hours to obtain a clear PZT sol.
[0053] (3) Spin coating PZT sol to fill the alumina template
[0054] The PZT sol was deposited in the alumina template (circular sheet with a diameter of 1 cm) by using a glue machine. The centrifugal force of the glue machine was used to make the PZT sol adhere to the wall of the cylindrical alumina hole, while the center of the cylinder remained hollow. To achieve this effect, the working parameters of the glue machine were: low speed 500 rpm for 5 seconds, high speed 3000 rpm for 25 seconds;
[0055] After each pass of coating, the alumina template was dried on a hot plate at 150 °C for 6 min and then annealed at 700 °C in air for 4 min;
[0056] The above process was repeated twice to obtain an alumina template with cylindrical alumina pores filled with PZT and a hollow center.
[0057] (4) Use a magnetron sputtering deposition apparatus to deposit a metal platinum nanolayer on the PZT surface and in the center of the PZT nanocolumn, and electro-deposit metal nickel on the platinum surface as a supporting layer
[0058] Platinum metal was deposited using a magnetron sputtering deposition apparatus, and the deposition parameters were: DC power supply, 10 W sputtering power, room temperature, working gas pressure 0.5 Pa, argon gas flow rate 40 sccm, and sputtering time 1 min;
[0059] Deposit Ni, use an electrochemical workstation to deposit a Ni support layer, the electrodeposition solution contains NiSO4 (0.38M), NiCl2 (0.12M) and H3BO3 (0.5M), the electrodeposition procedure is constant current deposition, the aluminum base layer on the back of the alumina template cannot contact the electrodeposition solution, leaving only the PZT spin-coated surface in contact with the electrodeposition solution, first use a small current of 20mA to deposit for 1 hour, then use a large current of 40mA to deposit for 5 hours, and finally use 200mA to deposit for 1 hour;
[0060] During the electrodeposition process, bubbles will adhere to the sample surface. Use a rubber-tipped dropper to blow away the bubbles in time.
[0061] (5) Remove the metal aluminum substrate and the aluminum oxide template layer
[0062] Remove the aluminum substrate, place the back side of the sample obtained in the previous step, i.e., the aluminum substrate surface, in a mixed solution of CuCl2 / HCl (water and concentrated hydrochloric acid in a volume ratio of 1:1, and a CuCl2 concentration of 0.15 M), and use a rubber-tipped dropper to suck the CuCl2 / HCl solution to continuously rinse and remove the aluminum substrate. The sample surface on which the metal nickel is deposited cannot contact the CuCl2 / HCl mixed solution;
[0063] The sample with the aluminum substrate removed was turned over with the metal nickel support layer facing downward, and placed in a 2M NaOH solution. It was left to soak at room temperature for 4 hours to completely remove the aluminum oxide template and obtain a vertical ordered nanocolumn array structure PZT photoelectrode.
[0064] The prepared photoelectrode was subjected to photoelectrochemical testing using a three-electrode system:
[0065] The prepared photoelectrode was used as the working electrode, the platinum sheet was used as the counter electrode, and the Ag / AgCl was used as the reference electrode. The electrolyte was a 0.5 M Na2SO4 aqueous solution (pH 6.8). A xenon lamp light source equipped with an AM1.5G filter was used, and the light intensity was adjusted to 100 mW / cm 2 , and conduct photoelectrochemical tests.
[0066] Example 2
[0067] A method for preparing a ferroelectric photoelectrode with a vertical ordered nanocolumn array structure comprises the following steps:
[0068] (1) Preparation of alumina template
[0069] The aluminum sheet was cleaned, and the aluminum sheet was used as the anode and the lead plate was used as the cathode. The aluminum sheet was placed in a mixed solution of perchloric acid HClO4 and ethanol C2H5OH with a volume ratio of 1:7, and magnetic stirring was performed at -10°C, and the voltage was 20V for 5 minutes to remove the surface oxide layer and obtain a mirror-polished aluminum sheet.
[0070] The polished aluminum sheet is used as an anode and the lead plate is used as a cathode. The aluminum sheet is oxidized in a 0.3M oxalic acid aqueous solution at 5°C, the voltage is 40V, and the oxidation time is 8 hours to obtain a primary oxide layer; the aluminum sheet containing the primary oxide layer is placed in a mixed solution of 6wt.% phosphoric acid H3PO4 and 1.8wt.% chromic acid H2CrO4 for corrosion treatment at a temperature of 60°C for 12 hours, and after removing the primary oxide layer, an aluminum sheet with nano-pits on the surface is obtained;
[0071] An aluminum sheet with nano-pits on the surface was used as an anode and a lead plate was used as a cathode. The aluminum sheet was oxidized in a 0.3M oxalic acid aqueous solution at 5°C, with a voltage of 40V and an oxidation time of 25min to obtain an initial aluminum oxide template. The template was then transferred to a 5wt.% dilute phosphoric acid solution and immersed at 45°C for 35min to expand the pores. The template was then rinsed with deionized water to obtain an aluminum oxide template.
[0072] (2) Preparation of ferroelectric Pb(Zr 0.2 Ti 0.8 )O3(PZT)sol
[0073] 4.17 g (CH3COO)2Pb·3H2O (99.99%) was dissolved in 15 g CH3COOH and dehydrated to 10 g at 200°C to obtain lead sol;
[0074] 0.93 g C 12 H 28 O4Zr (70wt%) and 14.13g C3H8O2 were stirred and mixed evenly, and 2.7g C 16 H 36 O4Ti, and then add 0.5ml of chelating agent (C5H8O2) to prepare zirconium titanium (ZT) sol;
[0075] 1.4 ml of deionized water (>18 MΩ) and an equal volume of C3H8O2 were mixed to obtain a hydrolyzed sol;
[0076] After the lead sol is cooled to room temperature, the ZT sol is added to the lead sol under low-speed stirring. After stirring for one hour, the hydrolyzed sol is added dropwise and stirred for another 4 hours. Finally, the sol is aged at room temperature for 24 hours to obtain a clear PZT sol.
[0077] (3) Spin coating PZT sol to fill the alumina template
[0078] The PZT sol was deposited in the alumina template (circular sheet with a diameter of 1 cm) by using a glue spreader. The centrifugal force of the glue spreader was used to make the PZT sol adhere to the wall of the cylindrical alumina hole, while the center of the cylinder remained hollow. To achieve this effect, the working parameters of the glue spreader were: low speed 500 rpm for 5 seconds, high speed 5000 rpm for 25 seconds;
[0079] After each coating, the alumina template was dried on a hot plate at 200°C for 4 minutes, and then annealed in air at 580°C for 6 minutes. The above process was repeated 4 times to obtain an alumina template with cylindrical alumina pores filled with PZT on the wall and hollow in the center.
[0080] (4) Use a magnetron sputtering deposition apparatus to deposit a metal platinum nanolayer on the PZT surface and the center of the PZT nanocolumn, and then electrodeposit metal nickel on the platinum surface as a supporting layer
[0081] Platinum metal was deposited using a magnetron sputtering deposition apparatus. The deposition experimental parameters were: DC power supply, 20 W sputtering power, room temperature, working gas pressure 0.7 Pa, argon gas flow rate 50 sccm, and sputtering time 2 min.
[0082] The Ni support layer was deposited using an electrochemical workstation. The electrodeposition solution contained NiSO4 (0.38 M), NiCl2 (0.12 M) and H3BO3 (0.5 M). The electrodeposition procedure was constant current deposition. The aluminum substrate layer on the back of the alumina template could not contact the electrodeposition solution. Only the PZT spin-coated surface was left in contact with the electrodeposition solution. First, a small current of 20 mA was used for deposition for 2 hours, then a large current of 45 mA was used for deposition for 8 hours, and finally a 200 mA was used for deposition for 3 hours.
[0083] During the electrodeposition process, bubbles will adhere to the sample surface. Use a rubber-tipped dropper to blow away the bubbles in time.
[0084] (5) Remove the metal aluminum substrate and the aluminum oxide template layer
[0085] Remove the aluminum substrate, place the back side of the sample obtained in the previous step, i.e., the aluminum substrate surface, in a mixed solution of CuCl2 / HCl (water and concentrated hydrochloric acid in a volume ratio of 1:1, and a CuCl2 concentration of 0.15 M), and use a rubber-tipped dropper to suck the CuCl2 / HCl solution to continuously rinse and remove the aluminum substrate. The sample surface on which the metal nickel is deposited cannot contact the CuCl2 / HCl mixed solution;
[0086] The sample with the aluminum substrate removed was turned over with the metal nickel support layer facing downward, and placed in a 2M NaOH solution. It was left to soak at room temperature for 8 hours to completely remove the alumina template and obtain a vertical ordered nanocolumn array structure PZT photoelectrode.
[0087] The prepared photoelectrode was subjected to photoelectrochemical testing using a three-electrode system:
[0088] The prepared photoelectrode was used as the working electrode, the platinum sheet was used as the counter electrode, and the Ag / AgCl was used as the reference electrode. The electrolyte was a 0.5 M Na2SO4 aqueous solution (pH 6.8). A xenon lamp light source equipped with an AM1.5G filter was used, and the light intensity was adjusted to 100 mW / cm 2 , and conduct photoelectrochemical tests.
[0089] Example 3
[0090] A method for preparing a ferroelectric photoelectrode with a vertical ordered nanocolumn array structure comprises the following steps:
[0091] (1) Preparation of alumina template:
[0092] The aluminum sheet was cleaned, and the aluminum sheet was used as an anode and a lead plate as a cathode. The aluminum sheet was placed in a mixed solution of perchloric acid HClO4 and ethanol C2H5OH with a volume ratio of 1:7, and magnetic stirring was performed at -10°C, and the voltage was 20V for 7 minutes to remove the surface oxide layer and obtain a mirror-polished aluminum sheet.
[0093] The polished aluminum sheet is used as an anode and the lead plate is used as a cathode, and oxidation is performed in a 0.3M oxalic acid aqueous solution at 5°C, a voltage of 40V, and an oxidation time of 12h to obtain a primary oxide layer; the primary oxide layer is removed, and the aluminum sheet containing the primary oxide layer is placed in a mixed solution of 6wt.% phosphoric acid H3PO4 and 1.8wt.% chromic acid H2CrO4 for corrosion treatment at a temperature of 60°C for 15h to obtain an aluminum sheet with nano-pits on the surface;
[0094] An aluminum sheet with nano-pits on the surface was used as an anode and a lead plate was used as a cathode. The aluminum sheet was oxidized in a 0.3M oxalic acid aqueous solution at 5°C, with a voltage of 40V and an oxidation time of 40min to obtain an initial aluminum oxide template. The template was then transferred to a 5wt.% dilute phosphoric acid solution and immersed at 45°C for 50min to expand the pores. The template was then rinsed with deionized water to obtain an aluminum oxide template.
[0095] (2) Preparation of ferroelectric Pb(Zr 0.2 Ti 0.8 )O3(PZT)sol
[0096] 6.17 g (CH3COO)2Pb·3H2O (99.99%) was dissolved in 15 g CH3COOH and dehydrated to 10 g at 250°C to obtain lead sol;
[0097] 1.53 g C 12 H 28 O4Zr (70wt%) and 14.13g C3H8O2 were stirred and mixed evenly, and 4.7g C 16 H 36 O4Ti, and then add 1ml of chelating agent (C5H8O2) to prepare zirconium titanium (ZT) sol;
[0098] 3 ml of deionized water (>18 MΩ) and an equal volume of C3H8O2 were mixed to obtain a hydrolyzed sol;
[0099] After the lead sol was cooled to room temperature, the ZT sol was added to the lead sol under low-speed stirring. After stirring for one hour, the hydrolyzed sol was added dropwise and stirred for another 6 hours. Finally, the sol was aged at room temperature for 48 hours to obtain a clear PZT sol.
[0100] (3) Spin coating PZT sol to fill the alumina template
[0101] The PZT sol was deposited in the alumina template (circular piece with a diameter of 1 cm) using a glue machine. The centrifugal force of the glue machine was used to make the PZT sol adhere to the wall of the cylindrical alumina hole, while the center of the cylinder remained hollow. To achieve this effect, the working parameters of the glue machine were: low speed 500rpm for 5 seconds, high speed 6000rpm for 25 seconds. After each glue spread, the alumina template was dried on a hot plate at 250℃ for 2 minutes, and then annealed in air at 400℃ for 10 minutes;
[0102] The above process was repeated 6 times to obtain an alumina template with cylindrical alumina pores filled with PZT and a hollow center.
[0103] (4) Use a magnetron sputtering deposition apparatus to deposit a metal platinum nanolayer on the PZT surface and the center of the PZT nanocolumn, and then electrodeposit metal nickel on the platinum surface as a supporting layer
[0104] Platinum metal was deposited using a magnetron sputtering deposition apparatus. The deposition experimental parameters were: DC power supply, 30 W sputtering power, room temperature, working gas pressure 0.9 Pa, argon gas flow rate 60 sccm, and sputtering time 5 min.
[0105] Deposit Ni, use an electrochemical workstation to deposit a Ni support layer, the electrodeposition solution contains NiSO4 (0.38M), NiCl2 (0.12M) and H3BO3 (0.5M), the electrodeposition procedure is constant current deposition, the aluminum base layer on the back of the alumina template cannot contact the electrodeposition solution, leaving only the PZT spin-coated surface in contact with the electrodeposition solution, first use a small current of 20mA to deposit for 3 hours, then use a large current of 50mA to deposit for 10 hours, and finally use 200mA to deposit for 5 hours;
[0106] During the electrodeposition process, bubbles will adhere to the sample surface. Use a rubber-tipped dropper to blow away the bubbles in time.
[0107] (5) Remove the metal aluminum substrate and the aluminum oxide template layer
[0108] Remove the aluminum substrate, place the back side of the sample obtained in the previous step, i.e., the aluminum substrate surface, in a mixed solution of CuCl2 / HCl (water and concentrated hydrochloric acid in a volume ratio of 1:1, and a CuCl2 concentration of 0.15 M), and use a rubber-tipped dropper to suck the CuCl2 / HCl solution to continuously rinse and remove the aluminum substrate. The sample surface on which the metal nickel is deposited cannot contact the CuCl2 / HCl mixed solution;
[0109] The sample with the aluminum substrate removed was turned over with the metal nickel support layer facing downward, and placed in a 2M NaOH solution. It was left to soak at room temperature for 12 hours to completely remove the aluminum oxide template and obtain a vertical ordered nanocolumn array structure PZT photoelectrode.
[0110] The prepared photoelectrode was subjected to photoelectrochemical testing using a three-electrode system:
[0111] The prepared photoelectrode was used as the working electrode, the platinum sheet was used as the counter electrode, and the Ag / AgCl was used as the reference electrode. The electrolyte was a 0.5 M Na2SO4 aqueous solution (pH 6.8). A xenon lamp light source equipped with an AM1.5G filter was used, and the light intensity was adjusted to 100 mW / cm 2 , and conduct photoelectrochemical tests.
[0112] Comparison of the photoelectrochemical test results (linear sweep voltammetry curves) obtained in the above three embodiments shows that the vertical ordered nanorod array PZT photoelectrode prepared in Embodiment 2 has the largest photocurrent density.
[0113] The practical effect of the present invention is supported by experimental data.
[0114] Figure 2 The SEM images of the PZT plane structure and the PZT nanocolumn structure are shown in Figure 2. Figure 2 A shows the low-magnification SEM top view of the PZT planar structure. PZT forms a uniform film with a smooth surface on the ITO film (207nm). Its high-magnification SEM top view shows that its surface structure is a film made of 20-100nm-sized PZT grains laid flat ( Figure 2 B), with a thickness of about 600nm ( Figure 2 B illustration). Figure 2 C shows a low-magnification SEM top view of the PZT nanocolumn structure, which is an orderly arranged nanocolumn structure with a diameter of about 80 nm. Figure 2 As shown in D and its inset, it is obvious that the vertically ordered structure is formed. The height of the nanopillars is about 800 nm, the center-to-center distance between the nanopillars is about 92 nm, and the density of the nanopillars is about 2×10 10 Pieces / cm 2 .
[0115] Figure 3A is the X-ray diffraction (XRD) spectrum of the PZT plane structure and the PZT nanorod structure. The successful construction of the PZT nanorod was further confirmed by XRD characterization from the perspective of the crystal phase structure. The diffraction peaks of the PZT nanorods at diffraction angles of 22.5°, 31.3°, 38.8°, 43.7°, 45.8° and 56.6° show the polycrystalline perovskite structure of the PZT nanorods, and its polycrystalline structure is consistent with JCPDS No.70-4260 (Pb(Zr 0.2 Ti 0.8 Compared with the PZT plane (ITO substrate), no impurity peaks were found except for the diffraction peak of the supporting layer nickel, indicating that a high-purity PZT nanorod array structure was successfully prepared.
[0116] Figure 3 B is the hysteresis loop diagram of the highly ordered PZT nanorod array prepared by the present invention, showing the hysteresis loop shape of a slender relaxor ferroelectric, the remanent polarization value is significantly smaller than the maximum polarization value, and the 2 times remanent polarization value (2Pr) reaches 30μC / cm 2 The high remnant polarization of ferroelectrics gives them the ability to induce a strong polar charge-induced electric field, which can drive the separation of photogenerated charges. This is the key to using ferroelectric-based materials as efficient PEC photoelectrodes for hydrogen production from water.
[0117] Figure 4 This is the comparison result of the photoelectrochemical activity test of PZT planar structure and PZT nanocolumn structure photoelectrode. Figure 4 A is the linear sweep voltammetry curve of each photoelectrode. The prepared PZT planar structure only shows -20μA / cm at 0V vs.RHE. 2 The photocurrent density of the PZT nanorod structure photoelectrode prepared by the present invention reaches -400μA / cm 2 , compared with the PZT planar structure, it is increased to 20 times. Figure 4The photoelectric conversion efficiency (ABPE) value under applied bias shown in B shows that the PZT nanopillar structure photoelectrode can reach its maximum ABPE value (0.45%) at a lower bias (0.2V vs. RHE), which is the saturation voltage value, while the saturation voltage of the PZT planar structure is 0.3V vs. RHE) and the maximum ABPE value is 0.05%. Obviously, in terms of photoelectric conversion efficiency, the conversion efficiency of the PZT nanopillar structure is 9 times that of the PZT planar structure. The negative shift of the saturation voltage indicates that the charge carrier separation and migration in the PZT nanopillar structure is faster than that in the PZT planar structure, which can be attributed to the high aspect ratio structure of the nanopillar array, which orthogonalizes the light absorption direction with the carrier transport direction, greatly improving the separation and transportation efficiency of the carriers, while ensuring the thickness of the PZT light absorption layer and the PZT ferroelectric polarization field to separate the photogenerated carriers.
[0118] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a ferroelectric photoelectrode with a vertical ordered nanorod array structure, It is characterized in that The steps include: (1) Preparation of ferroelectric Pb(Zr 0.2 Ti 0.8 ) 3 (PZT) Sol (a) 2.17-6.17 g (CH 3 COO 2 Pb·3H 2 O is dissolved in 15g of glacial acetic acid, dehydrated to 10g at 150-250℃, and cooled to room temperature to obtain lead sol; (b) 0.53-1.53 g C 12 H 28 O 4 Zr and 14.13g ethylene glycol monomethyl ether were stirred and mixed evenly, and 1.7-4.7g C 16 H 36 O 4 Ti, and then add 0.2-1 ml of chelating agent acetylacetone to obtain zirconium-titanium ZT sol; (c) mixing 1 to 3 ml of deionized water and an equal volume of ethylene glycol monomethyl ether to obtain a hydrolyzed sol; (d) Add ZT sol to lead sol under low-speed stirring and continue stirring for 1 hour, then add hydrolyzed sol drop by drop and continue stirring for 2 to 6 hours. Then age at room temperature for 12 to 48 hours to obtain a clear ferroelectric Pb(Zr 0.2 Ti 0.8 ) 3 PZT sol; (2) Spin coating PZT sol to fill the alumina template Spin-coating the PZT sol onto the surface of the circular alumina template to obtain a cylindrical alumina template with PZT filled in the pore walls and a hollow center; The circular alumina template is a laminated sheet with a base layer of metal aluminum and a surface layer of aluminum oxide. The surface of the aluminum oxide surface layer is distributed with a number of cylindrical holes of uniform size, the pore diameter is adjustable in the range of 60 to 150 nm, the pore depth is adjustable in the range of 300 to 1000 nm and does not penetrate the base layer; (3) Deposit a metal platinum nanolayer on the PZT surface and in the center of the PZT nanocolumn, and then electrodeposit metal nickel on the platinum surface as a supporting layer ① Magnetron sputtering deposition of metal platinum Pt, the working parameters of the magnetron sputtering deposition instrument are: DC power supply, sputtering power of 10-30W, room temperature, working gas pressure of 0.5-0.9Pa, argon flow rate of 40-60sccm, and sputtering time of 1-5min; ② Constant current electrochemical deposition of nickel metal Ni to obtain a nickel support layer. The electrodeposition solution contains 0.38M NiSO 4 , 0.12 M NiCl 2 and 0.5 M H 3 BO 3 , the aluminum base layer of the alumina template does not contact the electrodeposition solution, only the PZT spin-coated surface contacts, a small current of 20mA is deposited for 1 to 3h → a large current of 40 to 50mA is deposited for 5 to 10h → a 200mA is deposited for 1 to 5h; (4) Remove the aluminum base layer and the aluminum oxide template to obtain a ferroelectric photoelectrode with a vertical ordered nanocolumn array structure.
2. The method for preparing the ferroelectric photoelectrode with a vertical ordered nanorod array structure according to claim 1, Features: Step (a), 2.17-6.17 g (CH 3 COO 2 Pb·3H 2 O is dissolved in 15g of glacial acetic acid, dehydrated to 10g at 200℃, and cooled to room temperature to obtain lead sol.
3. The method for preparing the ferroelectric photoelectrode with a vertical ordered nanorod array structure according to claim 1, Features: Step (b), the C 12 H 28 O 4 The concentration of Zr is 70wt%.
4. The method for preparing the ferroelectric photoelectrode with a vertical ordered nanorod array structure according to claim 1, Features: In step (c), the resistivity of the deionized water is >18 MΩ.
5. The method for preparing the ferroelectric photoelectrode with a vertical ordered nanorod array structure according to claim 1, Features: Step (2), the working parameters of the glue spreader are: low speed 500 rpm for 5 seconds, high speed 3000-6000 rpm for 25 seconds; after each glue spread, the alumina template is first dried on a hot plate at 150-250°C for 2-6 minutes, and then annealed in an air environment at 400-700°C for 4-10 minutes; this is repeated 2-10 times.
6. The method for preparing the ferroelectric photoelectrode with a vertical ordered nanorod array structure according to claim 5, Features: Step (2), after each coating, the alumina template is first dried on a hot plate at 200°C for 4 minutes and then annealed in air at 580°C for 6 minutes.
7. The method for preparing the ferroelectric photoelectrode with a vertical ordered nanorod array structure according to claim 1, Features: Step (4), placing the aluminum base layer of the aluminum oxide template obtained in step (3) on a CuCl 2 / HCl mixed solution, the aluminum base layer is continuously washed away, and the sample surface on which the metal nickel is deposited does not contact CuCl 2 / HCl mixed solution; turn the alumina template after removing the aluminum base layer, with the metal nickel support layer facing downward, and place it completely in a 2M NaOH solution, let it stand at room temperature for 4 to 12 hours, and remove the alumina template.
8. The method for preparing the ferroelectric photoelectrode with a vertical ordered nanorod array structure according to claim 7, Features: Step (4), the CuCl 2 The mixed solution of CuCl is water and concentrated hydrochloric acid in a volume ratio of 1:
1. 2 The concentration is 0.15M.
9. A ferroelectric photoelectrode having a vertical ordered nanorod array structure prepared by the method according to any one of claims 1 to 8, Features: The photoelectric device has a vertical ordered nanocolumn array structure supported by metal nickel, wherein the metal nickel is an electrode support layer, and its structure is a combination of a metal nickel planar layer and a metal nickel nanocolumn array layer. The metal platinum nanolayer closely attached to the metal nickel nanocolumn array layer is a bottom electrode layer, and the PZT nanolayer is closely attached to the platinum nanolayer, and the PZT nanolayer is an extremely vertically ordered PZT nanocolumn array structure.
10. An application of the ferroelectric photoelectrode having a vertical ordered nanorod array structure as claimed in claim 9, Features: It is applied to efficient PEC water splitting to produce hydrogen.
